2020
DOI: 10.1007/s13399-020-01000-9
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from co-pyrolysis of urban organic wastes—investigation of carbon sink potential using ATR-FTIR and TGA

Abstract: Urban organic wastes (UOW) strain the infrastructures for solid waste treatment (SWT) in emerging economies. This study investigated biochar gained from three major UOW sources in India—banana peduncles (BP), a fibrous waste, from fruit markets; sewage sludge (SS) from wastewater treatment plants; and anaerobic digestate (AD) from food and market waste processing facilities—in terms of its potential to sequester and become long-term carbon sink in soils. Herein, the chemical properties (using ATR-FTIR) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“…During pyrolysis, anaerobic food digestates contain the highest concentrations of stable phosphorus and chloride, which may increase the digestate's oxidative stability. However, a mixture of the three substrates had the highest carbon sink potential than their individual potential (Nair et al 2020). As a result, biocharderived digestate has the potential to be an efficient carbon sink during carbon dioxide removal.…”
Section: Role Of Biochar From Digestate In Climate Change Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…During pyrolysis, anaerobic food digestates contain the highest concentrations of stable phosphorus and chloride, which may increase the digestate's oxidative stability. However, a mixture of the three substrates had the highest carbon sink potential than their individual potential (Nair et al 2020). As a result, biocharderived digestate has the potential to be an efficient carbon sink during carbon dioxide removal.…”
Section: Role Of Biochar From Digestate In Climate Change Mitigationmentioning
confidence: 99%
“…The increased aromaticity indicated that the biochar was more stable and resistant to microorganism decomposition (Leng et al 2019). Nair et al (2020) examined biochar's carbon sequestration potential and biochar's ability to act as a long-term carbon sink in soils. Biochar was produced from three organic wastes: banana fibrous waste, sewage sludge from wastewater treatment, and anaerobic food digestate.…”
Section: Role Of Biochar From Digestate In Climate Change Mitigationmentioning
confidence: 99%
“…The substrates are collected, oven-dried (at 105 • C), and sampled as detailed in a previous study [21]. The average particle size is kept at 0.2 mm to minimize the effect of transport phenomena [4].…”
Section: Materials Usedmentioning
confidence: 99%
“…Pyrolysis characteristics are analyzed using a TGA/DSC 3+ LF thermogravimetric analyzer (Mettler Toledo, Greifensee, Switzerland). Instrument calibration is performed as in [21]. About 10 ± 1 mg of each sample is loaded in a 70 µL alumina crucible without compression.…”
Section: Tga-dscmentioning
confidence: 99%
“…In application of ATR FT-IR spectroscopy to characterize biochars generated from various agricultural by-products, Liu et al (2015) proposed a simple 3-band algorithm (R readings) per multi-point averages of the band intensities at respective ranges of 1750-1500 cm -1 , 2000-1790 cm -1 , and 645-655 cm -1 . While the FT-IR analysis of Liu et al (2015) has been applied to qualitative characterization of biochars from various agricultural and industrial wastes and byproducts (e.g., Li et al, 2020b;Nair et al, 2020;Rodriguez et al, 2020), the quantitative evaluation by the R reading has not been adopted. This is mainly due to the two facts that 1) its physical significance is not apparent as the idea was derived from three-band ratio algorithms in cotton fiber and cellulose studies (Liu et al, 2011;Nam et al, 2017), and 2) Liu et al (2015) did not report clear correlations between R readings and pyrolysis temperature of the four types of plant biomass biochars they generated.…”
Section: Atr Ft-ir Spectramentioning
confidence: 99%